2022
DOI: 10.1007/s13222-022-00426-x
|View full text |Cite
|
Sign up to set email alerts
|

Testing Very Large Database Management Systems: The Case of SAP HANA

Abstract: Software Testing is an established activity in the software development process to ensure and improve the quality of a software. Consequently, there exists a wide range of literature, popular information, and even multiple ISO standards covering this topic. However, we found that testing very large database management systems (DBMS) requires special adaptations of the generally available guidance for software testing and requires to solve specific challenges that may not be relevant for other areas or smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Previous studies on in-memory computing have demonstrated its efficacy in various applications. For instance, SAP HANA, one of the leading in-memory computing platforms (Bach et al, 2022), has been shown to accelerate database processing times by orders of magnitude compared to disk-based systems. Researchers have also explored the scalability aspects of in-memory computing, focusing on how distributed architectures can be leveraged to handle growing data loads without compromising performance.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Previous studies on in-memory computing have demonstrated its efficacy in various applications. For instance, SAP HANA, one of the leading in-memory computing platforms (Bach et al, 2022), has been shown to accelerate database processing times by orders of magnitude compared to disk-based systems. Researchers have also explored the scalability aspects of in-memory computing, focusing on how distributed architectures can be leveraged to handle growing data loads without compromising performance.…”
Section: Background and Related Workmentioning
confidence: 99%